Controlled Surface Mineralization of Metal Oxides on Nanofibers† - Horzum Polat, Nesrin; Demir, Mustafa Muammer; Mari, Margherita; Wagner, Manfred; Fortunato, Giuseppino; Popa, Ana-Maria; Demir, Mustafa Muammer; Landfester, Katharina; Crespy, Daniel; Mu˜noz-Espi, Rafael (Royal Society of Chemistry, 2015)
We report a versatile approach for the preparation of metal oxide/polymer hybrid nanofibers by in situ formation of metal oxide nanoparticles on surface-functionalized polymer fibers. Poly (styrene-covinylphosphonic acid) fibers were produced by electrospinning and used as supports for the in situ formation of ceria nanocrystals without further thermal treatment. The crystallization of ceria was induced by the addition of an alkaline solution to fibers loaded with the corresponding precursor. The formation of the inorganic material at the fiber surface was investigated by transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). The extension of the approach to prepare polymer/titania hybrid nanofibers demonstrates its versatility.
Keywords: Polymer fibers; Metal oxides; Nanofibers; Cerium oxides; Titania